Opieka okulistyczna w Nepalu - Nowak, Rafał (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Perched on the greatest heights of the Himalayas Nepal is a small landlocked country, placed between Tibet and India. Cataract is the main cause of blindness in the Nepalese population. On the other hand, very few of us realize that this poor country has been able to develop an interesting, specific and relatively good eye care service system. The aim of this study is the complete analysis of this subject in regard to its structure, funding and training of medical personnel.